Women struggle to secure land rights - Mary Kimani (Africa Renewal, 2008)
Felitus Kures is a widow living in Kapchorwa, northeastern Uganda. Her husband’s death left her solely responsible for their children. To meet their needs, she depended on the small piece of land she and her husband had farmed together. But just months after his funeral, her in-laws sold her husband’s land without her knowledge. “We only realized this when the buyer came to evict us,” Ms. Kures explains. She was able to regain use of the land after she got legal assistance with the help of the Uganda Land Alliance, a civil society group that campaigns for land rights.